SISTEM PERTANAHAN TRADISIONAL PADA MASYARAKAT BATAK TOBA DAN RELEVANSINYA DI KAWASAN DANAU TOBA (ANALISIS SOSIOLOGIS) - Harisan Boni Firmando (Jurnal Ilmiah Sosiologi Agama (JISA), 2021)
Land is a very valuable capital so that people can live and carry out their activities. There are two main functions of land, namely as a production function and a non-production function. The purpose of this study was to determine the meaning and function of land in the Toba Batak community and to understand the land ownership system which includes land as inheritance and traditional land tenure transfers in the Lake Toba area. The research uses qualitative methods to understand social phenomena. The results showed that the local wisdom of the community about land is regulated by adat, namely land as private property, inheritance as well as public needs. The traditional land system of the Toba Batak people is still relevant today. The traditional land system can be seen from the sociological and historical aspects experienced by the people in the Lake Toba area. This is reinforced by the current rapid developments in the Lake Toba area which require the Toba Batak people to show their identity based on local wisdom.